Prokaryotic epizoic profiles of diseased corals and detection of the causative agent of porites ulcerative white spot (PUWS) coral disease in the Lingayen Gulf, Philippines - Arboleda, Mark Dondi M. (Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
Coral diseases have become an increasing threat to the stability of coral reef ecosystems. In search for microbiological indicators of coral health and coral diseases, community profiles of coral-associated epizoic prokaryotes were investigated because of their dual potential as a source both of coral pathogens and their antagonists.